Методичні аспекти аналізу ефективності використання матеріальних ресурсів на підприємстві - Рубан, Ліна Олегівна; Федоренко, Ірина Анатоліївна (Національний технічний університет "Харківський політехнічний інститут", 2017)
У статті розглянуто мету та завдання аналізу матеріальних ресурсів на промислових підприємствах, висвітлено основні етапи аналізу ефективності використання матеріальних ресурсів. Запропоновано методичний підхід до формування системи показників ефективності використання матеріальних ресурсів промислового підприємства на основі виділення чотирьох груп показників: узагальнюючі показники ефективності, індивідуальні (часткові) показники ефективності, показники фінансової результативності, факторні моделі матеріаловіддачі та матеріаломісткості.

The goal and tasks of the analysis of material resources in industrial enterprises are considered in the article, the main stages of the analysis of the efficiency of the use of material resources are covered. A methodical approach to the formation of a system of indicators of the effectiveness of the use of material resources of an industrial enterprise based on the identification of four groups of indicators is proposed: generalizing indicators of the effectiveness of the use of material resources, individual (partial) indicators of the efficiency of the use of material resources, indicators of the financial performance of the use of material resources, factor models of return materials and specific consumption of materials. The use of this system parameters makes it possible to implement an integrated approach to analyzing the efficiency of use of material resources, that explore the process of consumption of material resources in the context of sustainable development of enterprises.
Methodical aspects of the analysis of the efficiency of the use of material resources in the enterprise
Keywords: матеріальні витрати; оборотність; матеріаломісткість; матеріаловіддача; material resources; material costs; turnover; efficiency; specific consumption of materials; return materials